2021
DOI: 10.21833/ijaas.2021.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Process improvement methodology selection in manufacturing: A literature review perspective

Abstract: Problems in manufacturing have always been a hurdle for leadership, engineers, and professionals. They can lead to low productivity, poor quality, high costs, and ultimately loss of customers. Problems should be prevented by fair means and following well-established methodologies of continuous process improvement. The present paper addresses this topic, which in both academic and professional literature has been discussed from one single angle–that is, how to use a specific methodology in a certain situation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…This can be explained as the right strategy can improve succeeding operational activities. Appropriate planning leads to effective application and maintenance according to the concepts of systematic problem solving approaches such as PDCA, DMAIC and 8D (Aichouni et al ., 2021; Tamher et al. , 2021; Kholif et al ., 2018).…”
Section: Finding and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This can be explained as the right strategy can improve succeeding operational activities. Appropriate planning leads to effective application and maintenance according to the concepts of systematic problem solving approaches such as PDCA, DMAIC and 8D (Aichouni et al ., 2021; Tamher et al. , 2021; Kholif et al ., 2018).…”
Section: Finding and Discussionmentioning
confidence: 99%
“…This can be explained as the right strategy can improve succeeding operational activities. Appropriate planning leads to effective application and maintenance according to the concepts of systematic problem solving approaches such as PDCA, DMAIC and 8D (Aichouni et al, 2021;Tamher et al, 2021;Kholif et al, 2018). This is similar to the concept of management systems such as ISO 22301, ISO 14001 and the cleaner production and environmental management system (ISO 22301:2019(ISO 22301: , 2022Campos, 2012;UNEP/UNIDO, 2004;Oliveira et al, 2017).…”
Section: Componentsmentioning
confidence: 94%
See 2 more Smart Citations
“…An extensive literature review was performed and indicated that a large number of process improvement methodologies are available for manufacturing [16]. The study showed that the PDCA and the six sigma DMAIC methodologies present superior performance in problem-solving and process improvement compared to other improvement models.…”
Section: Methodsmentioning
confidence: 99%